2015
DOI: 10.1101/gad.252189.114
|View full text |Cite
|
Sign up to set email alerts
|

Screen identifies bromodomain protein ZMYND8 in chromatin recognition of transcription-associated DNA damage that promotes homologous recombination

Abstract: How chromatin shapes pathways that promote genome-epigenome integrity in response to DNA damage is an issue of crucial importance. We report that human bromodomain (BRD)-containing proteins, the primary ''readers'' of acetylated chromatin, are vital for the DNA damage response (DDR). We discovered that more than one-third of all human BRD proteins change localization in response to DNA damage. We identified ZMYND8 (zinc finger and MYND [myeloid, Nervy, and DEAF-1] domain containing 8) as a novel DDR factor tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
327
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(356 citation statements)
references
References 72 publications
(113 reference statements)
28
327
1
Order By: Relevance
“…In contrast, by examining multiple endogenous cut sites, Aymard et al found a significant increase in HR when DSBs were located in euchromatic regions and/or next to actively transcribed genes (70). Similar results were also reported by Gong et al (71). While our study does not directly address repair pathway choice for DSBs, we do show an association between DDX1 and efficient repair by HR that is linked to transcription and the presence of RNA at DSBs.…”
Section: Discussionsupporting
confidence: 46%
“…In contrast, by examining multiple endogenous cut sites, Aymard et al found a significant increase in HR when DSBs were located in euchromatic regions and/or next to actively transcribed genes (70). Similar results were also reported by Gong et al (71). While our study does not directly address repair pathway choice for DSBs, we do show an association between DDX1 and efficient repair by HR that is linked to transcription and the presence of RNA at DSBs.…”
Section: Discussionsupporting
confidence: 46%
“…Previous studies have reported that ZMYND8 is a functional component of the transcription repression complex NuRD (58,59) and targets it to the DNA damage response site (23). CHD3/4 is responsible for the ATPdependent chromatin remodeling function of NuRD (35,60).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported as a novel DNA damage response factor that recruits NuRD complex to damaged chromatin (23). Its involvement in chromatin template-dependent processes, viz.…”
Section: Zmynd8 Is a Histone H3/h4-interacting Protein-mentioning
confidence: 99%
See 1 more Smart Citation
“…5), including with ZMYND8, ZNF687, ZNF592, and BRD4. These proteins were also linked to ZNF532 in data from previous mass spectrometric analyses (26)(27)(28). Interestingly, the ZMYND8 locus, encoding a top interactor of ZNF532, is bound by NUT-fusion proteins in all NMC lines tested (selected examples are shown in Fig.…”
Section: Znf532-nut Forms Megadomains Of Hyperacetylated Chromatinmentioning
confidence: 99%